Underground spaces unveiled : planning and creating the cities of the future - Admiraal, Han; Cornaro, Antonia (ICE Publishing, 2018)
'Underground Spaces Unveiled' is a broad overview of the concept of underground space development investigating the issues that are associated with the sustainable development of urban underground space.